2019
DOI: 10.3390/molecules24173135
|View full text |Cite
|
Sign up to set email alerts
|

DFT Investigations of the Vibrational Spectra and Translational Modes of Ice II

Abstract: The vibrational spectrum of ice II was investigated using the CASTEP code based on first-principles density functional theory (DFT). Based on good agreement with inelastic neutron scattering (INS), infrared (IR), and Raman experimental data, we discuss the translation, libration, bending, and stretching band using normal modes analysis method. In the translation band, we found that the four-bond and two-bond molecular vibration modes constitute three main peaks in accordance with INS ranging from 117 to 318 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…We have reviewed the vibrational normal modes of ice XV and clarified the physical aspects of its exotic vibrational modes . The distributions of vibrational modes in ice XV are similar to those we have determined in our previous series of studies, such as ice VII and VIII, and the hydrogen-bonding modes in the translational band also obey the theory of two types of hydrogen bonds. Based on a successful investigation of ice XV, in this study, we constructed an ice VI supercell, explored its atomic and molecular vibrational modes, and compared these modes with those of ice XV. A comparative analysis was also reported in the meaning of an experimental method.…”
Section: Introductionsupporting
confidence: 57%
“…We have reviewed the vibrational normal modes of ice XV and clarified the physical aspects of its exotic vibrational modes . The distributions of vibrational modes in ice XV are similar to those we have determined in our previous series of studies, such as ice VII and VIII, and the hydrogen-bonding modes in the translational band also obey the theory of two types of hydrogen bonds. Based on a successful investigation of ice XV, in this study, we constructed an ice VI supercell, explored its atomic and molecular vibrational modes, and compared these modes with those of ice XV. A comparative analysis was also reported in the meaning of an experimental method.…”
Section: Introductionsupporting
confidence: 57%
“…For the dynamic processes, please see the Supporting Information. Later, we also found this phenomenon in ice XIV, XVI, XVII, VIII, VII, II, and XV. Herein, we explained the two peaks of the most common phase, ice Ih, by comparative analysis with ice XI.…”
Section: Resultsmentioning
confidence: 78%
“…The INS spectrum showed two distinct Hbond peaks at atmospheric pressure and in some high-pressure ice phases. 21 After a series of investigations, we deduced that these two distinct H-bond peaks were derived from two kinds of H-bond vibrational modes, namely, four-bond and two-bond modes, rather than from two H-bond force constants, as proposed by Li et al [23][24][25][26][27][28]32 In all ice phases, each water molecule is linked to four neighboring water molecules via Hbonds, forming a tetrahedral structure. In the ideal model of hydrogen-ordered ice Ic, the central molecule in the four-bond mode vibrates along the H−O−H angle bisector, while the four neighboring molecules vibrate in the opposite direction.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…21 We disagreed with this view 22 and proposed a theory of two intrinsic H-bond vibrational modes. 23 On the basis of a series of studies of ice Ic, 23 II, 24 VII, 25 VIII, 26 X, 27 XV, 28 and others, we deduced that this is a general rule for vibrational modes of the ice family. In this study, we demonstrated how to analyze hydrogen-disordered complex ice V using first-principles density functional theory simulations.…”
Section: ■ Introductionmentioning
confidence: 78%